FACTOR OF DELEGITIMIZATION IN THE PROCESS OF DESTABILIZATION OF THE POLITICAL REGIME - Шиян, О. М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The factors of legitimation and delegitimization of power in the context of the functioning of transitional states are considered and analyzed. The peculiarity of such states is the problem of consolidation of citizens on the basis of common values, the absence of which gradually leads to the delegitimization of the political regime. Particular attention is paid to classical and modern interpretations of legitimacy and related concepts. An understanding of the definition of «legitimacy» is given as an order in which the power of the rulers and the voluntary subordination of the governed, i.e. free recognition by each member of the legal society. It is established that there are different political institutions with different levels of legitimacy in society. The main factors and phases of legitimacy are analyzed, on the example of Ukraine, allocated factors that lead to the delegitimization of a political regime. The problem of the functioning of the institutional process in the post-Soviet states through the phenomenon of double institutionalization, which is characterized by public consent to the functioning of old and new institutions at the same time, is considered separately. The nature of such a phenomenon, which is characterized by a destructive impact on the democratic transformation of society due to the congestion of the new institutional space, has been established. A number of factors of delegitimization of the political regime are analyzed and the classification of factors into economic, geographical, political. The dependence of different factors on different conditions of power is determined. The peculiarity of the delegitimization process in Ukraine, which is characterized by multifactorial with elements of adaptability, has been established. Based on all the theories presented, it is concluded that legitimacy is not only a set of values, it has both cognitive and normative aspects.